Reversible dysregulation of renal circadian rhythm in lupus nephritis - Rakesh Mishra; Ramalingam Bethunaickan; Celine C. Berthier; Zhengzi Yi; Joshua J. Strohl; Patricio T. Huerta; Weijia Zhang; Anne Davidson (BMC, 2021)
Abstract Background We have found disruption of expression of major transcriptional regulators of circadian rhythm in the kidneys of several mouse models of lupus nephritis. Here we define the consequence of this disturbance with respect to circadian gene expression and renal homeostatic function in a mouse model of lupus nephritis. Methods Molecular profiling of kidneys from 47 young and 41 nephritic female NZB/W F1 mice was performed at 4 hourly intervals over a 24 h period. Disruption of major circadian transcriptional regulators was confirmed by qPCR. Molecular data was normalized and analyzed for rhythmicity using RAIN analysis. Serum aldosterone and glucose and urine sodium and potassium were measured at 4 hourly intervals in pre-nephritic and nephritic mice and blood pressure was measured every 4 h. Analyses were repeated after induction of complete remission of nephritis using combination cyclophosphamide and costimulatory blockade. Results We show a profound alteration of renal circadian rhythms in mice with lupus nephritis affecting multiple renal pathways. Using Cosinor analysis we identified consequent alterations of renal homeostasis and metabolism as well as blood pressure dipper status. This circadian dysregulation was partially reversed by remission induction therapy. Conclusions Our studies indicate the role of inflammation in causing the circadian disruption and suggest that screening for loss of normal blood pressure dipping should be incorporated into LN management. The data also suggest a potential role for circadian agonists in the treatment of lupus nephritis.